A short review on bimetallic Co-based catalysts for carbon dioxide reforming of methane - Mahadi, Bahari; H. D., Setiabudi; N., Ainirazali; Vo, Dai-Viet N. (Elsevier Ltd., 2021)
The development of catalysts that afford excellent catalytic performance along with high resistance toward coke accumulation is fundamental in carbon dioxide reforming of methane (CDRM). Apart from Ni-based catalysts, the Co-based catalysts gained significant attention in CDRM accredited to the Co’s capability in improving catalytic stability and lowering the coke formation. However, the lower catalytic activities of Co-based catalysts when compared to Ni-based catalysts in reforming works are the real challenges that need to be solved. In this study, a short review of various approaches that have been implemented by researchers for improving the catalytic performance issues related to Co-based catalysts is presented. This paper also presents recent Co-bimetallic catalysts approached, covers the catalyst activity as well as issues related to catalyst deactivation when compared to Co monometallic catalysts. In addition, the outlook of the related bimetallic Co-based catalysts has been proposed to provide more critical information.